Laugier-Hunziker Syndrome: An Uncommon Cause of Oral Pigmentation and a Review of the Literature - Lucio Montebugnoli; Ivana Grelli; Fabio Cervellati; Cosimo Misciali; Beatrice Raone (International Journal of Dentistry)
Laugier-Hunziker syndrome is a rare benign condition characterized by diffuse oral hyperpigmentation associated with pigmentation of the nails. The syndrome must be included in the differential diagnosis of diffuse oral pigmentation to exclude other conditions with systemic implications. We describe a 43-year-old white woman with the clinical and histological features of Laugier-Hunziker syndrome associated with toenail pigmentation. The correct clinical identification avoids the need for detailed investigations and treatment. We also review the potential causes of oral pigmentation.